Super-hydrophobic nano coating and preparation method thereof

By preparing a coating liquid containing fluorinated solid microspheres and spraying it on the substrate surface, the problem that existing superhydrophobic coatings are difficult to achieve low rolling angles, and superhydrophobic nanocoatings with high contact angles and low rolling angles are achieved. Ensure the surface is clean and dry.

CN119463642AActive Publication Date: 2025-02-18HARBIN INST OF TECH TAIZHOU INST OF INNOVATION & TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411591984.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

Existing superhydrophobic coatings are difficult to achieve low rolling angles, causing droplets to retention on the surface, affecting surface cleaning and drying.

Method used

By preparing a coating liquid containing fluorinated solid microspheres, epoxy resin and curing agent, it is coated on the substrate surface by spraying technology, and a superhydrophobic nanocoating with uniform roughness is obtained by thermal curing.

Benefits of technology

A contact angle of up to 159.2° and a rolling angle of only 0.6° are achieved, ensuring that droplets roll and fall off quickly on the coating surface, preventing liquid from retention and keeping the surface clean and dry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125830320000091
    Figure BDA0005125830320000091
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to a super-hydrophobic nano coating and a preparation method thereof. The coating is obtained by spraying a coating liquid on the surface of a substrate and then carrying out thermocuring; the coating liquid is prepared from the following components in parts by weight: 8 to 12 parts of fluorinated solid microspheres, 3 to 4 parts of epoxy resin, 0.5 to 1 part of a curing agent, 0.2 to 0.5 part of trimethylolpropane triglycidyl ether and 20 to 30 parts of acetone; the fluorinated solid microspheres are obtained by carrying out emulsion polymerization on glycidyl methacrylate, aminated nano silicon dioxide and 4-vinylaniline. The coating provided by the invention shows super-hydrophobic performance and has an extremely low rolling angle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a super-hydrophobic nano coating and a preparation method thereof. Background Art

[0002] In recent years, super-hydrophobic materials have become a hot topic in materials science research due to their wide application prospects in the fields of anti-fouling, waterproofing, and self-cleaning. Super-hydrophobic phenomena in nature, such as the lotus effect, have inspired scientists to study surface roughness and chemical composition. Artificial super-hydrophobic coatings achieve excellent performance with a contact angle of more than 150° by adjusting surface roughness and chemical properties, and can effectively resist the attachment of aqueous liquids.

[0003] The preparation of super-hydrophobic coatings usually requires a combination of chemical modification and microstructure design. In current technology, common preparation methods include sol-gel method, electrochemical deposition method and spraying technology. By refining the structural design of nanoparticles and introducing chemical functional groups, a surface structure with both micron and nanometer roughness can be constructed, thereby enhancing super-hydrophobic properties.

[0004] While achieving high contact angles is relatively easy, achieving low sliding angles is a more challenging task. The sliding angle is closely related to the roughness uniformity of the coating surface. High contact angles can usually be achieved through simple chemical modifications, but low sliding angles require the coating surface to have a highly uniform roughness structure to ensure that the droplet can roll freely on the surface without being stuck. Summary of the invention

[0005] In view of this, the purpose of the present invention is to propose a super-hydrophobic nano-coating and a preparation method thereof, so as to provide a super-hydrophobic nano-coating with uniform roughness, so that it has an extremely low rolling angle, which helps the droplets to roll and fall off quickly on the coating surface, thereby effectively preventing the liquid from being retained on the surface. This property is very important for keeping the surface clean and dry, especially in application scenarios that require waterproofing and anti-fouling, such as building exterior walls, car windshields, and electronic equipment casings.

[0006] Based on the above purpose, the present invention provides a super hydrophobic nano coating, which is obtained by spraying a coating liquid on a substrate surface and then thermally curing;

[0007] Further, the coating liquid comprises the following components by weight: 8-12 parts of fluorinated solid microspheres, 3-4 parts of epoxy resin, 0.5-1 part of curing agent, 0.2-0.5 parts of trimethylolpropane triglycidyl ether and 20-30 parts of acetone;

[0008] Furthermore, the preparation steps of the fluorinated solid microspheres are as follows:

[0009] (1) using 3-aminopropyltriethoxysilane to modify nano-silica to obtain amino-modified nano-silica;

[0010] (2) adding glycidyl methacrylate, azobisisobutyronitrile, and amino-modified nano-silica to 4-vinylaniline, stirring at 30-40° C. for 20-40 min, adding an emulsifier, stirring for 20-40 min, heating to 50-60° C., adding a polyvinyl alcohol aqueous solution, stirring for 30-50 min, heating to 80-90° C., stirring for 5-7 h, cooling to room temperature, filtering, washing, and vacuum drying to obtain solid microspheres;

[0011] (3) adding the solid microspheres to 1,2-dichloroethane, stirring for 20-40 min, then adding glycidyl ether hexafluorononyl ether, stirring at 45-55° C. for 20-40 min, filtering, washing, and vacuum drying to obtain fluorinated solid microspheres.

[0012] Preferably, during the spraying, the nozzle is 20-30 cm away from the substrate and the spraying pressure is 4-5 KPa.

[0013] Preferably, the epoxy resin is bisphenol A epoxy resin.

[0014] Preferably, the curing agent is diethylenetriamine, triethylenetetramine or a mixture of the two.

[0015] Preferably, in step (1), the weight ratio of 3-aminopropyltriethoxysilane to nano-silicon dioxide is 0.05-0.2:2.

[0016] Preferably, the average particle size of the nano-silicon dioxide in step (1) is 20-100 nm.

[0017] Preferably, the concentration of the polyvinyl alcohol aqueous solution in step (2) is 2wt%-4wt%.

[0018] Preferably, the emulsifier in step (2) is a mixture of Span-80 and Tween-80 in a weight ratio of 1:9.

[0019] Preferably, in step (2), the weight ratio of glycidyl methacrylate, azobisisobutyronitrile, amino-modified nano-silica, 4-vinylaniline, emulsifier and polyvinyl alcohol aqueous solution is 3:0.1:2:10:1:40.

[0020] Preferably, in step (3), the weight ratio of the solid microspheres, 1,2-dichloroethane and glycidyl ether hexafluorononyl ether is 10:80-120:0.1-1.

[0021] Furthermore, the present invention provides a method for preparing a super-hydrophobic nano-coating, and the specific steps are as follows: adding fluorinated solid microspheres, bisphenol A epoxy resin, triethylenetetramine, and propylene glycol triglycidyl ether to acetone to obtain a coating liquid, and then using a spray gun to spray the coating liquid onto the surface of a stainless steel substrate, first curing at 55-65°C for 15-30 minutes, and then curing at 75-85°C for 1.5-2.5 hours to obtain a super-hydrophobic nano-coating.

[0022] Beneficial effects of the present invention:

[0023] The super-hydrophobic nano-coating of the present invention achieves remarkable hydrophobic performance through multiple chemical modifications and structural optimization, specifically a contact angle of up to 159.2° and a rolling angle of only 0.6°. These properties are derived from the highly rough structure of the coating surface, which forms an air cushion effect, can effectively capture air, and enhance the super-hydrophobicity of the coating.

[0024] The 4-vinylaniline used in the present invention provides multiple reaction sites: by cross-linking with glycidyl methacrylate, the uniformity of the solid microspheres is enhanced; as a grafting site for glycidyl ether hexafluorononyl ether, a fluorine chain with low surface energy is introduced; and by cross-linking with the epoxy resin in the coating matrix, the solid microspheres are evenly distributed on the coating surface. These chemical reactions and physical modifications work synergistically to greatly improve the superhydrophobic properties of the coating.

[0025] The amino-modified silicon dioxide introduced in the present invention is effectively dispersed evenly on the surface of the solid microspheres to form a nano-scale structure, which complements the micron-scale solid microspheres to construct a micro-nano rough surface, further improving the super-hydrophobic effect of the coating. In addition, the fluorination of the solid microspheres further reduces the surface energy, forming a better low-wettability surface. DETAILED DESCRIPTION

[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0027] Embodiment 1:

[0028] (1) 2 g of nano-silicon dioxide with an average particle size of 80 nm was added to a mixed solution of 10 g of anhydrous ethanol and 20 g of deionized water, and ultrasonicated for 20 min, and then 0.05 g of 3-aminopropyltriethoxysilane was added, and stirred at 45° C. for 6 h, centrifuged, and washed with deionized water 3 times, washed with anhydrous ethanol 3 times, and vacuum dried to obtain amino-modified nano-silicon dioxide;

[0029] (2) 1 g of glycidyl methacrylate, 0.05 g of azobisisobutyronitrile, and 1 g of amino-modified nano-silica were added to 10 g of 4-vinylaniline, and stirred at 30° C. for 20 min. 0.05 g of Span-80 and 0.45 g of Tween-80 were added, and stirred for 20 min. The mixture was heated to 50° C., 30 g of a 3 wt % aqueous solution of polyvinyl alcohol 1788 was added, and stirred for 30 min. The mixture was heated to 80° C. and stirred for 5 h. The mixture was cooled to room temperature, filtered, and washed with deionized water 3 times, with anhydrous ethanol 3 times, and dried in vacuo to obtain solid microspheres.

[0030] (3) adding 10 g of solid microspheres to 80 g of 1,2-dichloroethane, stirring for 20 min, then adding 0.1 g of glycidyl ether hexafluorononyl ether, stirring at 45 °C for 20 min, filtering, washing with anhydrous ethanol three times, and vacuum drying to obtain fluorinated solid microspheres;

[0031] (4) 8 g of fluorinated solid microspheres, 3 g of bisphenol A epoxy resin, 0.5 g of diethylenetriamine, and 0.2 g of trimethylolpropane triglycidyl ether were added to 20 g of acetone to obtain a coating liquid, which was then sprayed onto the surface of a stainless steel substrate using a spray gun. The nozzle was 20 cm away from the substrate and the spraying pressure was 4 KPa. The coating was first cured at 60 ° C for 20 min and then cured at 80 ° C for 2 h to obtain a super hydrophobic nano coating.

[0032] Embodiment 2:

[0033] (1) adding 2 g of nano-silicon dioxide with an average particle size of 80 nm to a mixed solution of 10 g of anhydrous ethanol and 20 g of deionized water, ultrasonicating for 20 min, then adding 0.1 g of 3-aminopropyltriethoxysilane, stirring at 45° C. for 6 h, centrifuging, washing with deionized water 3 times, washing with anhydrous ethanol 3 times, and vacuum drying to obtain amino-modified nano-silicon dioxide;

[0034] (2) 3 g of glycidyl methacrylate, 0.1 g of azobisisobutyronitrile, and 2 g of amino-modified nano-silica were added to 10 g of 4-vinylaniline, stirred at 35° C. for 30 min, then 0.1 g of Span-80 and 0.9 g of Tween-80 were added, stirred for 30 min, then the temperature was raised to 55° C., 40 g of a 3 wt % aqueous solution of polyvinyl alcohol 1788 was added, stirred for 40 min, the temperature was raised to 85° C., stirred for 6 h, cooled to room temperature, filtered, washed with deionized water 3 times, washed with anhydrous ethanol 3 times, and vacuum dried to obtain solid microspheres;

[0035] (3) adding 10 g of solid microspheres to 100 g of 1,2-dichloroethane, stirring for 30 min, then adding 0.5 g of glycidyl ether hexafluorononyl ether, stirring at 50° C. for 30 min, filtering, washing with anhydrous ethanol three times, and vacuum drying to obtain fluorinated solid microspheres;

[0036] (4) 10 g of fluorinated solid microspheres, 3.5 g of bisphenol A epoxy resin, 0.7 g of triethylenetetramine, and 0.35 g of trimethylolpropane triglycidyl ether were added to 25 g of acetone to obtain a coating liquid, which was then sprayed onto the surface of a stainless steel substrate using a spray gun. The nozzle was 25 cm away from the substrate and the spraying pressure was 4.5 KPa. The coating was first cured at 60 ° C for 20 min and then cured at 80 ° C for 2 h to obtain a super hydrophobic nano coating.

[0037] Embodiment 3:

[0038] (1) adding 2 g of nano-silicon dioxide with an average particle size of 80 nm to a mixed solution of 10 g of anhydrous ethanol and 20 g of deionized water, ultrasonicating for 20 min, then adding 0.2 g of 3-aminopropyltriethoxysilane, stirring at 45° C. for 6 h, centrifuging, washing with deionized water 3 times, washing with anhydrous ethanol 3 times, and vacuum drying to obtain amino-modified nano-silicon dioxide;

[0039] (2) 5 g of glycidyl methacrylate, 0.2 g of azobisisobutyronitrile, and 3 g of amino-modified nano-silica were added to 10 g of 4-vinylaniline, stirred at 40° C. for 40 min, then 0.2 g of Span-80 and 1.8 g of Tween-80 were added, stirred for 40 min, then the temperature was raised to 60° C., 50 g of a 4 wt % aqueous solution of polyvinyl alcohol 1788 was added, stirred for 50 min, the temperature was raised to 90° C., stirred for 7 h, cooled to room temperature, filtered, washed with deionized water 3 times, washed with anhydrous ethanol 3 times, and vacuum dried to obtain solid microspheres;

[0040] (3) adding 10 g of solid microspheres to 120 g of 1,2-dichloroethane, stirring for 30 min, then adding 1 g of glycidyl ether hexafluorononyl ether, stirring at 55 °C for 40 min, filtering, washing with anhydrous ethanol three times, and vacuum drying to obtain fluorinated solid microspheres;

[0041] (4) 12 g of fluorinated solid microspheres, 4 g of bisphenol A epoxy resin, 1 g of triethylenetetramine, and 0.5 g of trimethylolpropane triglycidyl ether were added to 30 g of acetone to obtain a coating liquid, which was then sprayed onto the surface of a stainless steel substrate using a spray gun. The nozzle was 30 cm away from the substrate and the spraying pressure was 5 KPa. The coating was first cured at 60 ° C for 20 min and then cured at 80 ° C for 2 h to obtain a super hydrophobic nano coating.

[0042] Comparative Example 1:

[0043] The difference between Comparative Example 1 and Example 2 is that 4-vinylaniline is replaced by styrene;

[0044] The specific steps are as follows:

[0045] (1) adding 2 g of nano-silicon dioxide with an average particle size of 80 nm to a mixed solution of 10 g of anhydrous ethanol and 20 g of deionized water, ultrasonicating for 20 min, then adding 0.1 g of 3-aminopropyltriethoxysilane, stirring at 45° C. for 6 h, centrifuging, washing with deionized water 3 times, washing with anhydrous ethanol 3 times, and vacuum drying to obtain amino-modified nano-silicon dioxide;

[0046] (2) 3 g of glycidyl methacrylate, 0.1 g of azobisisobutyronitrile, and 2 g of amino-modified nano-silica were added to 10 g of styrene, stirred at 35° C. for 30 min, then 0.1 g of Span-80 and 0.9 g of Tween-80 were added, stirred for 30 min, then heated to 55° C., 40 g of a 3 wt % aqueous solution of polyvinyl alcohol 1788 was added, stirred for 40 min, heated to 85° C., stirred for 6 h, cooled to room temperature, filtered, washed with deionized water 3 times, washed with anhydrous ethanol 3 times, and vacuum dried to obtain solid microspheres;

[0047] (3) adding 10 g of solid microspheres to 100 g of 1,2-dichloroethane, stirring for 30 min, then adding 0.5 g of glycidyl ether hexafluorononyl ether, stirring at 50° C. for 30 min, filtering, washing with anhydrous ethanol three times, and vacuum drying to obtain fluorinated solid microspheres;

[0048] (4) 10 g of fluorinated solid microspheres, 3.5 g of bisphenol A epoxy resin, 0.7 g of triethylenetetramine, and 0.35 g of trimethylolpropane triglycidyl ether were added to 25 g of acetone to obtain a coating liquid, which was then sprayed onto the surface of a stainless steel substrate using a spray gun. The nozzle was 25 cm away from the substrate and the spraying pressure was 4.5 KPa. The coating was first cured at 60°C for 20 min and then cured at 80°C for 2 h to obtain a nano coating.

[0049] Comparative Example 2:

[0050] The difference between Comparative Example 2 and Example 2 is that the silicon dioxide is not amino-treated;

[0051] The specific steps are as follows:

[0052] (1) 3 g of glycidyl methacrylate, 0.1 g of azobisisobutyronitrile, and 2 g of nano-silica with an average particle size of 80 nm were added to 10 g of 4-vinylaniline, and stirred at 35° C. for 30 min. 0.1 g of Span-80 and 0.9 g of Tween-80 were added, and stirred for 30 min. The temperature was then raised to 55° C., 40 g of a 3 wt % aqueous solution of polyvinyl alcohol 1788 was added, and stirred for 40 min. The temperature was raised to 85° C., and stirred for 6 h. The mixture was cooled to room temperature, filtered, and washed with deionized water 3 times, washed with anhydrous ethanol 3 times, and vacuum dried to obtain solid microspheres.

[0053] (2) adding 10 g of solid microspheres to 100 g of 1,2-dichloroethane, stirring for 30 min, then adding 0.5 g of glycidyl ether hexafluorononyl ether, stirring at 50° C. for 30 min, filtering, washing with anhydrous ethanol three times, and vacuum drying to obtain fluorinated solid microspheres;

[0054] (3) 10 g of fluorinated solid microspheres, 3.5 g of bisphenol A epoxy resin, 0.7 g of triethylenetetramine, and 0.35 g of trimethylolpropane triglycidyl ether were added to 25 g of acetone to obtain a coating liquid, which was then sprayed onto the surface of a stainless steel substrate using a spray gun. The nozzle was 25 cm away from the substrate and the spraying pressure was 4.5 KPa. The coating was first cured at 60°C for 20 min and then cured at 80°C for 2 h to obtain a nano coating.

[0055] Comparative Example 3:

[0056] The difference between Comparative Example 3 and Example 2 is that glycidyl methacrylate is not added;

[0057] The specific steps are as follows:

[0058] (1) adding 2 g of nano-silicon dioxide with an average particle size of 80 nm to a mixed solution of 10 g of anhydrous ethanol and 20 g of deionized water, ultrasonicating for 20 min, then adding 0.1 g of 3-aminopropyltriethoxysilane, stirring at 45° C. for 6 h, centrifuging, washing with deionized water 3 times, washing with anhydrous ethanol 3 times, and vacuum drying to obtain amino-modified nano-silicon dioxide;

[0059] (2) 0.1 g of azobisisobutyronitrile and 2 g of amino-modified nano-silica were added to 13 g of 4-vinylaniline, stirred at 35° C. for 30 min, then 0.1 g of Span-80 and 0.9 g of Tween-80 were added, stirred for 30 min, then the temperature was raised to 55° C., 40 g of a 3 wt % aqueous solution of polyvinyl alcohol 1788 was added, stirred for 40 min, the temperature was raised to 85° C., stirred for 6 h, cooled to room temperature, filtered, washed with deionized water 3 times, washed with anhydrous ethanol 3 times, and vacuum dried to obtain solid microspheres;

[0060] (3) adding 10 g of solid microspheres to 100 g of 1,2-dichloroethane, stirring for 30 min, then adding 0.5 g of glycidyl ether hexafluorononyl ether, stirring at 50° C. for 30 min, filtering, washing with anhydrous ethanol three times, and vacuum drying to obtain fluorinated solid microspheres;

[0061] (4) 10 g of fluorinated solid microspheres, 3.5 g of bisphenol A epoxy resin, 0.7 g of triethylenetetramine, and 0.35 g of trimethylolpropane triglycidyl ether were added to 25 g of acetone to obtain a coating liquid, which was then sprayed onto the surface of a stainless steel substrate using a spray gun. The nozzle was 25 cm away from the substrate and the spraying pressure was 4.5 KPa. The coating was first cured at 60°C for 20 min and then cured at 80°C for 2 h to obtain a nano coating.

[0062] Comparative Example 4:

[0063] The difference between Comparative Example 3 and Example 2 is that: the solid microspheres are not fluorinated;

[0064] The specific steps are as follows:

[0065] (1) adding 2 g of nano-silicon dioxide with an average particle size of 80 nm to a mixed solution of 10 g of anhydrous ethanol and 20 g of deionized water, ultrasonicating for 20 min, then adding 0.1 g of 3-aminopropyltriethoxysilane, stirring at 45° C. for 6 h, centrifuging, washing with deionized water 3 times, washing with anhydrous ethanol 3 times, and vacuum drying to obtain amino-modified nano-silicon dioxide;

[0066] (2) 3 g of glycidyl methacrylate, 0.1 g of azobisisobutyronitrile, and 2 g of amino-modified nano-silica were added to 10 g of 4-vinylaniline, stirred at 35° C. for 30 min, then 0.1 g of Span-80 and 0.9 g of Tween-80 were added, stirred for 30 min, then the temperature was raised to 55° C., 40 g of a 3 wt % aqueous solution of polyvinyl alcohol 1788 was added, stirred for 40 min, the temperature was raised to 85° C., stirred for 6 h, cooled to room temperature, filtered, washed with deionized water 3 times, washed with anhydrous ethanol 3 times, and vacuum dried to obtain solid microspheres;

[0067] (4) 10 g of solid microspheres, 3.5 g of bisphenol A epoxy resin, 0.7 g of triethylenetetramine, and 0.35 g of trimethylolpropane triglycidyl ether were added to 25 g of acetone to obtain a coating liquid, which was then sprayed onto the surface of a stainless steel substrate using a spray gun. The nozzle was 25 cm away from the substrate and the spraying pressure was 4.5 KPa. The coating was first cured at 60°C for 20 min and then cured at 80°C for 2 h to obtain a nano coating.

[0068] Performance Test:

[0069] Wettability test: The contact angle and rolling angle of the sample were tested using a contact angle meter. The results are shown in Table 1.

[0070] Surface roughness: The surface roughness of the samples was measured using a laser confocal microscope. Each coating was measured in three directions and the final roughness value was averaged. The results are shown in Table 1.

[0071] Table 1 Wettability and surface roughness

[0072]

[0073] Data Analysis:

[0074] It can be seen from the data of Examples 1-3 in Table 1 that the super-hydrophobic nano-coating prepared by the present invention has a contact angle as high as 159.2° and a rolling angle as low as 0.6°, showing excellent super-hydrophobicity. In addition, the surface roughness is relatively high, indicating that the surface has a rough structure, which is conducive to the capture of air by the coating on the surface of the sample, forming an air cushion on the surface of the coating to make the sample hydrophobic.

[0075] It can be seen from the data of Example 2 and Comparative Example 1 in Table 1 that 4-vinylaniline significantly increases the contact angle and decreases the rolling angle, which indicates that 4-vinylaniline helps to construct a uniform rough structure on the coating surface. This is mainly because 4-vinylaniline provides amino reaction sites. The amino reaction sites have three main functions. The first function is to form crosslinks with glycidyl methacrylate, thereby making the solid microspheres more uniform. The second function is to provide grafting sites for glycidyl ether hexafluorononyl ether to facilitate the introduction of fluorine chains with low surface energy. The third function is to crosslink with the epoxy resin in the coating matrix, thereby making the solid microspheres uniformly distributed on the coating surface. The above three functions synergistically promote excellent superhydrophobicity.

[0076] It can be seen from the data of Example 2 and Comparative Example 2 in Table 1 that the amination of silica helps to further improve the hydrophobicity. This is mainly because the amination silica can be evenly dispersed on the surface of the solid microspheres to form a nano-scale rough structure, which cooperates with the micron-scale rough structure caused by the solid microspheres to construct a micro-nano rough surface. The micro-nano rough surface has an important influence on the wettability of the coating.

[0077] It can be seen from the data of Example 2 and Comparative Example 3 in Table 1 that glycidyl methacrylate has a certain influence on the rolling angle of the coating. This is mainly due to the cross-linking effect of glycidyl methacrylate, which affects the distribution of amino-modified silica and the structure of the solid microspheres.

[0078] It can be seen from the data of Example 2 and Comparative Example 4 in Table 1 that the fluorination of the solid microspheres significantly reduces the wettability, which is mainly due to the introduction of low surface energy fluorine chains. The low surface energy fluorine chains and micro-nano structures synergistically construct a low wettability surface.

[0079] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A super hydrophobic nano coating, characterized in that: The coating liquid is sprayed on the surface of the substrate and then thermally cured; The coating liquid comprises the following components by weight: 8-12 parts of fluorinated solid microspheres, 3-4 parts of epoxy resin, 0.5-1 parts of curing agent, 0.2-0.5 parts of trimethylolpropane triglycidyl ether and 20-30 parts of acetone; The preparation steps of the fluorinated solid microspheres are as follows: (1) using 3-aminopropyltriethoxysilane to modify nano-silica to obtain amino-modified nano-silica; (2) adding glycidyl methacrylate, azobisisobutyronitrile, and amino-modified nano-silica to 4-vinylaniline, stirring at 30-40° C. for 20-40 min, adding an emulsifier, stirring for 20-40 min, heating to 50-60° C., adding a polyvinyl alcohol aqueous solution, stirring for 30-50 min, heating to 80-90° C., stirring for 5-7 h, cooling to room temperature, filtering, washing, and vacuum drying to obtain solid microspheres; (3) adding the solid microspheres to 1,2-dichloroethane, stirring for 20-40 minutes, then adding glycidyl ether hexafluorononyl ether, stirring at 45-55° C. for 20-40 minutes, filtering, washing, and vacuum drying to obtain fluorinated solid microspheres; In the step (2), the weight ratio of glycidyl methacrylate, azobisisobutyronitrile, amino-modified nano-silica, 4-vinylaniline, emulsifier and polyvinyl alcohol aqueous solution is 1-5:0.05-0.2:1-3:10:0.5-2:30-50.

2. The super-hydrophobic nano coating according to claim 1, characterized in that: During the spraying, the nozzle is 20-30 cm away from the substrate, and the spraying pressure is 4-5 KPa.

3. The super-hydrophobic nano coating according to claim 1, characterized in that: The epoxy resin is bisphenol A type epoxy resin.

4. The super-hydrophobic nano coating according to claim 1, characterized in that: The curing agent is one of diethylenetriamine and triethylenetetramine or a mixture of the two.

5. The super-hydrophobic nano coating according to claim 1, characterized in that: In the step (1), the weight ratio of 3-aminopropyltriethoxysilane to nano-silicon dioxide is 0.05-0.2:

2.

6. The super-hydrophobic nano coating according to claim 1, characterized in that: The average particle size of the nano-silicon dioxide in step (1) is 20-100 nm.

7. The super-hydrophobic nano coating according to claim 1, characterized in that: The concentration of the polyvinyl alcohol aqueous solution in step (2) is 2wt%-4wt%.

8. The super-hydrophobic nano coating according to claim 1, characterized in that: The emulsifier in step (2) is a mixture of Span-80 and Tween-80 in a weight ratio of 1:

9.

9. The super-hydrophobic nano coating according to claim 1, characterized in that: In the step (3), the weight ratio of the solid microspheres, 1,2-dichloroethane and glycidyl ether hexafluorononyl ether is 10:80-120:0.1-1.

10. A method for preparing a super-hydrophobic nano-coating according to any one of claims 1 to 9, characterized in that: The specific steps are as follows: add fluorinated solid microspheres, bisphenol A epoxy resin, triethylenetetramine, and propylene glycol triglycidyl ether into acetone to obtain a coating liquid, and then use a spray gun to spray the coating liquid onto the surface of a stainless steel substrate, first cure it at 55-65°C for 15-30 minutes, and then cure it at 75-85°C for 1.5-2.5 hours to obtain a superhydrophobic nano coating.

Citation Information

Patent Citations

  • Water-based fluoropolymer and silicon dioxide hybrid material and transparent super-amphiphobic coating prepared from same

    CN103408709A

  • Wear-resistant self-repairing super-hydrophobic coating as well as preparation method and application thereof

    CN113185886A

  • Porous powder loaded with super-hydrophobic particles as well as preparation method and application of porous powder

    CN113604095A

  • Preparation process of super-hydrophobic waterproof coating film

    CN116463040A

  • Method for Obtaining a Hybrid Latex and Use Thereof in Hydrophobic and Superhydrophobic Coatings

    US20170121442A1